2020
DOI: 10.1371/journal.pntd.0008746
|View full text |Cite
|
Sign up to set email alerts
|

Validation study of HLA-B*13:01 as a biomarker of dapsone hypersensitivity syndrome in leprosy patients in Indonesia

Abstract: Leprosy is a stigmatizing, chronic infection which degenerates the nervous system and often leads to incapacitation. Multi-drug therapy which consists of dapsone, rifampicin and clofazimine has been effective to combat this disease. In Indonesia, especially in Papua Island, leprosy is still a problem. Furthermore, there had been higher reports of Dapsone Hypersensitivity Syndrome (DHS) which also challenges leprosy elimination in certain aspects. Globally, DHS has a prevalence rate of 1.4% and a fatality rate … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 15 publications
(27 reference statements)
3
12
0
Order By: Relevance
“…These findings are also supported by another study conducted in Thailand for non-leprosy patients [185]. Similar trends were also found with leprosy patients in other parts of Asia concluded that HLA-B*13:01 allele was a strong predictor for dapsone induced SCARs including SJS/TEN or DRESS [186][187][188][189]. However, such genetic associations were not identified in European, Caucasian, American, African, or Oceanic population indicating that HLA-B*13:01 allele associated dapsone induced SCARs were only prevalent in Asian population especially in China and Southeast Asia.…”
Section: Dapsonesupporting
confidence: 84%
“…These findings are also supported by another study conducted in Thailand for non-leprosy patients [185]. Similar trends were also found with leprosy patients in other parts of Asia concluded that HLA-B*13:01 allele was a strong predictor for dapsone induced SCARs including SJS/TEN or DRESS [186][187][188][189]. However, such genetic associations were not identified in European, Caucasian, American, African, or Oceanic population indicating that HLA-B*13:01 allele associated dapsone induced SCARs were only prevalent in Asian population especially in China and Southeast Asia.…”
Section: Dapsonesupporting
confidence: 84%
“…By using GWAS approach, the susceptible gene of DHS was first found in Han Chinese with HLA-B * 13:01 (51), which mainly exists in Asians. The same result was validated in Koreans (52) and Indonesians (53). This gene was also susceptible in Thai with dapsone-induced SCARs (54), including DRESS and SJS/TEN (Table 1).…”
Section: Genetic Susceptibility To Aromatic Antiepileptic Drug-induced Severe Cutaneous Adverse Reactionssupporting
confidence: 61%
“…It is a rare life-threatening reaction globally with a range of incidence of 2% to 12% with a fatality rate of 9.9% (18). Due to the dominant HLA-B*13:01 carrier in Papuan ethnic groups, the incidence rate of DHS is highly reported among leprosy patients (11%) treated by dapsone as the significant component in MDT (19). It is necessary to improve effective engagement between leprosy health workers or dermatologists and the undergoing treatment patients and release from treatment (RFT) patients.…”
Section: Understanding the Urgency Of Leprosy -It Should Not Only Be ...mentioning
confidence: 99%